2019
DOI: 10.1242/jeb.190850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anoxia on ATP, water, ion and pH balance in an insect (Locusta migratoria)

Abstract: When exposed to anoxia, insects rapidly go into a hypometabolic coma from which they can recover when exposed to normoxia again. However, prolonged anoxic bouts eventually lead to death in most insects, although some species are surprisingly tolerant. Anoxia challenges ATP, ion, pH and water homeostasis, but it is not clear how fast and to what degree each of these parameters is disrupted during anoxia, nor how quickly they recover. Further, it has not been investigated which disruptions are the primary source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…This loss of coordinated spiracular control at low temperatures, and its re-establishment after rewarming, is consistent with prior observations of both chilled (Lalouette et al, 2011;MacMillan et al, 2012b) and frozen insects (Sinclair et al, 2004). Qualitatively, the pattern of _ V CO 2 during recovery from freezing in crickets bears a striking resemblance to insects recovering from anoxia, where spiracles are likely forced open by the acidification of hemolymph (Lighton and Schilman, 2007;Ravn et al, 2019;Woods and Lane, 2016). A similar acidification of hemolymph following freezing could explain these similarities.…”
Section: Metabolic Rate During Recovery From Cooling Freezing and Thawingsupporting
confidence: 88%
See 2 more Smart Citations
“…This loss of coordinated spiracular control at low temperatures, and its re-establishment after rewarming, is consistent with prior observations of both chilled (Lalouette et al, 2011;MacMillan et al, 2012b) and frozen insects (Sinclair et al, 2004). Qualitatively, the pattern of _ V CO 2 during recovery from freezing in crickets bears a striking resemblance to insects recovering from anoxia, where spiracles are likely forced open by the acidification of hemolymph (Lighton and Schilman, 2007;Ravn et al, 2019;Woods and Lane, 2016). A similar acidification of hemolymph following freezing could explain these similarities.…”
Section: Metabolic Rate During Recovery From Cooling Freezing and Thawingsupporting
confidence: 88%
“…While insect hemolymph acid-base status is usually well regulated, acid-base homeostasis can be disturbed by temperature and activity, among other factors (Harrison, 2001). For example, under anoxia, the insect hemolymph is acidified (Ravn et al, 2019), mostly likely by the accumulation of lactate (Woods and Lane, 2016), which liberates stored CO 2 as a burst (Lighton and Schilman, 2007) akin to what we observed in crickets at freezing (Fig. 1B).…”
Section: Origin Of Co 2 Release At Freezingsupporting
confidence: 62%
See 1 more Smart Citation
“…The migratory locust has been subject to various studies on pesticide resistance and hypoxia tolerance [ 43 , 89 ]. Various pesticides target AChE in order to disrupt synaptic signalling by acetylcholine, a major transmitter in insect sensory systems and central nervous neuropils.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative or complementary view of anoxia tolerance, more supported by studies with insects, is that variation in anoxia tolerance is related to differences in abilities to prevent or repair damage despite loss of most ATP. Insects deplete most of their ATP and ion gradients relatively quickly in anoxia, yet survive for many hours or even days (Wegener 1993; Krishnan et al 1997; Campbell et al 2018; Ravn et al 2019). Previous studies have indicated that mechanisms that protect against protein unfolding can be important in anoxia-tolerance, including induction of heat shock proteins (Azad et al 2011; Deng et al 2018), and trehalose (Chen et al 2002), suggesting that genes involved in coping with protein unfolding might be important in intraspecific variation in anoxia tolerance.…”
mentioning
confidence: 99%